2020
DOI: 10.3201/eid2609.201435
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Severe Acute Respiratory Syndrome Coronavirus 2 RNA on Surfaces in Quarantine Rooms

Abstract: S evere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread globally and, as of May 2, 2020, had caused >3 million confirmed coronavirus disease cases (1). Although SARS-CoV-2 transmission through respiratory droplets and direct contact is clear, the potential for transmission through contact with surfaces or objects contaminated with SARS-CoV-2 is poorly understood (2). The virus can be detected on various surfaces in the contaminated environment from symptomatic and paucisymptomatic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 14 publications
1
95
1
2
Order By: Relevance
“…Contamination with SARS-CoV-2 RNA has been found in multiple environmental sampling studies in hospitals, including contaminated surfaces and objects commonly used by staff (including footwear) [6,7,9]. Environmental contamination was also shown in 8/22 samples from a room of a pre-symptomatic patient [8]. Inability to detect contamination in isolation units [12,13] might demonstrate the success of extensive and frequent disinfection routines instituted in those hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination with SARS-CoV-2 RNA has been found in multiple environmental sampling studies in hospitals, including contaminated surfaces and objects commonly used by staff (including footwear) [6,7,9]. Environmental contamination was also shown in 8/22 samples from a room of a pre-symptomatic patient [8]. Inability to detect contamination in isolation units [12,13] might demonstrate the success of extensive and frequent disinfection routines instituted in those hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding enhanced hygiene and cleaning standards, it has been found that the COVID-19 virus remains infectious from hours to days on different types of surfaces, including plastic and stainless steel (Fa-Chun et al 2020;van Doremalen et al 2020). Therefore, physical contact with a contaminated surface is a potential mode of COVID-19 transmission.…”
Section: Hygiene Sanitization and Ventilationmentioning
confidence: 99%
“…22 studies were identified that conducted environmental sampling of SARS-CoV-2. Two studies were excluded as they were conducted outside of acute healthcare settings (one in a hotel quarantine facility, and one in community long-term care facilities) 18,28 . Of the 20 remaining studies (Table 5)…”
Section: Literature Review Of Environmental Sampling Studiesmentioning
confidence: 99%